A Methodology for Multilingual Automatic Item Generation - Gierl, Mark; Lai, Hollis (Mesure et évaluation en éducation)

(untitled) (ADMEE-Canada - Université Laval, 2015)
Testing agencies require large numbers of high-quality items that are produced in a cost-effective and timely manner. Increasingly, these agencies also require items in different languages. In this paper we present a methodology for multilingual automatic item generation (AIG). AIG is the process of using item models to generate test items with the aid of computer technology. We describe a three-step AIG approach where, first, test development specialists identify the content that will be used for item generation. Next, the specialists create item models to specify the content in the assessment task that must be manipulated to produce new items. Finally, elements in the item model are manipulated with computer algorithms to produce new items. Language is added in the item model step to permit multilingual AIG. We illustrate our method by generating 360 English and 360 French medical education items. The importance of item banking in multilingual test development is also discussed.